Prospective registry of adult patients receiving therapeutic plasma exchange with a presumptive diagnosis of thrombotic microangiopathy (TMA): the Turkish hematology research and education group (ThREG)-TMA02 study. (February 2022) - Akpinar, Seval; Tekgunduz, Emre; Esen, Ramazan; Yilmaz, Mehmet; Karakus, Volkan; Vural, Filiz; Gediz, Fusun; Aydogdu, Ismet; Kaynar, Leylagul; Goker, Hakan; Kelkitli, Engin; Ayyildiz, Orhan; et al.
Abstract: Thrombotic microanjiopathy (TMA) is a pathological diagnosis characterized by abnormalities of small vessels leading to microvascular thrombosis of arterioles and capillaries. The current prospective, non-interventional, multicenter study aimed to define the distribution of different TMA forms in adult Turkish patients who were referred for therapeutic plasma exchange (TPE) for presumptive diagnosis of TMA. Patients with serum ADAMTS13 activity <5% were diagnosed as having acquired thrombotic thrombocytopenic purpura (aTTP). Patients presenting with ADAMTS13 activity 6–10 % / normal renal function and patients with ADAMTS13 activity >10 %, normal renal function and no secondary TMA were treated as unclassified TMA. The study included a total of 80 patients (women: 50; man: 30) with a median age of 48 (20−74). Detailed evaluation at 1 month after hospital admission revealed aTTP, secondary TMA, infection/complement-associated hemolytic uremic syndrome and unclassified TMA in 29 (36.2 %), 22 (27.5 %), 23 (28.8 %) and 6 (7.5 %) patients respectively. As subclassification of various TMAs will dictate specific therapy, proper diagnosis in a timely manner is of utmost clinical significance.